Solar panel energy technology for sustainable agriculture farming: A review - Aroonsrimorakot, S.; Laiphrakpam, M.; Paisantanakij, W. (International Journal of Agricultural Technology, 2020)
Agriculture is very important to human beings because it is the sole provider of food for human. However, agricultural processes require constant energy resources for machineries operation, irrigation pumps, greenhouse heating. All of these are conventionally operated using fossil fuel. The use of fossil fuel in agricultural farms accelerates climate changes as it emits lots of greenhouse gases. This made scientists, researchers and academicians to find an alternative and sustainable agricultural farming using renewable energy such as solar panel energy technology to mitigate the environmental problems that may result to global warming and climate change. Furthermore, to solve the alarming fear of exhaustion of fossil fuel. The authors present this article by reviewing literatures from various available sources. The article concludes that there is the need to conduct more researches in order to optimize the combination of solar panel energy technology application and agricultural cultivation among the agricultural farmers due to its environmental as well as economic feasibility.